Pendampingan Literasi Digital Berkelanjutan untuk Guru dan Siswa Melalui Perpustakaan Digital di SDIT ANNIDA - Anshor, Abdul Halim; Rezeki, Fitri; Rismawati; Erdi; Fauzi, Ahmad (Jurnal Pelita Pengabdian, 2025)
Improving digital literacy skills plays a crucial role in equipping educators and students to adapt to the rapidly advancing developments in information technology. However, many educational institutions still face obstacles such as limited resources, inability to use digital technology, and lack of guidance. The purpose of this community service program is to introduce and implement a digital library as a means to improve sustainable digital literacy for teachers and students at SDIT ANNIDA. This will involve initial observation, technical training, mentoring in the use of a web-based digital library system, and a participant evaluation of the program's benefits. The results of the program indicate that teachers and students have improved skills in accessing and utilizing digital information. Furthermore, the digital library system has stimulated student interest in e-reading and improved use of digital collections. This program can be implemented in other schools with similar conditions. However, several challenges must be overcome, such as adapting to technology and limited training time. To support digital transformation in elementary schools, a contextual and ongoing mentoring approach has proven useful.